(untitled) (International Journal of Engineering and Computer Science, 2015)
Border Gateway Protocol (BGP) is a standardized exterior gateway protocol designed to exchange routing and reachability information between autonomous systems (AS).The protocol is often classified as a path vector protocol but is sometimes also classed as a distance vector routing protocol. The Border Gateway Protocol does not involve traditional Interior Gateway Protocol (IGP) metrics, but makes routing decisions based on path, network policies and/or rule-sets configured by a network administrator. The Border Gateway Protocol plays a key role in the overall operation of the Internet and is involved in making core routing decisions. The Border Gateway Protocol is the successor to the Exterior Gateway Protocol (EGP) and is currently the most widely used exterior gateway protocol by Internet service provider (ISP) due to the fact that BGP allows for fully decentralised routing.